Capital Inflows, Credit Growth, and Financial Systems - Igan, Deniz (IMF Working Papers; Working Paper, 2015)
Exploiting a granular panel dataset that breaks down capital inflows into FDI, portfolio and other categories, and distinguishes between credit to the household sector and to the corporate sector, we investigate the association between capital inflows and credit growth. We find that non-FDI capital inflows boost credit growth and increase the likelihood of credit booms in both household and corporate sectors. For household credit growth, the composition of capital inflows appears to be more important than financial system characteristics. In contrast, for corporate credit growth, both the composition and the financial system matter. Regardless of sectors and financial systems, net other inflows are always linked to rapid credit growth. Firm-level data corroborate these findings and hint at a causal link: net other inflows are related to more rapid credit growth for firms that rely more heavily on external financing. Further explorations on how capital flows translate into more credit indicate that both demand and supply side factors play a role.